Magnetic catalysis versus magnetic inhibition - Fukushima, Kenji; Hidaka, Yoshimasa (Physical review letters, 2013)
We discuss the fate of chiral symmetry in an extremely strong magnetic field B. We investigate not only quark fluctuations but also neutral meson effects. The former enhances the chiral-symmetry breaking at finite B according to the magnetic catalysis, while the latter suppresses the chiral condensate once B exceeds the scale of the hadron structure. Using a chiral model, we demonstrate how neutral mesons are subject to the dimensional reduction and the low dimensionality favors the chiral-symmetric phase. We point out that this effect, the magnetic inhibition, can be a feasible explanation for recent lattice-QCD data indicating the decreasing behavior of the chiral-restoration temperature with increasing B.